2020
DOI: 10.1371/journal.pone.0235611
|View full text |Cite
|
Sign up to set email alerts
|

Origin of circulating free DNA in patients with lung cancer

Abstract: Liquid biopsy has become widely applied in clinical medicine along with the progress in innovative technologies, such as next generation sequencing, but the origin of circulating tumor DNA (ctDNA) has not yet been precisely established. We reported bimodal peaks of long fragment circulating free DNA (cfDNA) of 5 kb and short fragment cfDNA of 170 bp in patients with advanced lung cancer, and both contained ctDNA. In this paper, we demonstrate that the total amount of cfDNA is higher when patients with lung can… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(19 citation statements)
references
References 24 publications
(39 reference statements)
0
19
0
Order By: Relevance
“…A higher number of copies of mutants in cfDNA can be ascribed to the higher concentration of DNA obtained from plasma. Few earlier studies have reported a higher number of copies of mutant allele in cfDNA obtained from the supernatant left after extraction of EV than EV-DNA [10,13].…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…A higher number of copies of mutants in cfDNA can be ascribed to the higher concentration of DNA obtained from plasma. Few earlier studies have reported a higher number of copies of mutant allele in cfDNA obtained from the supernatant left after extraction of EV than EV-DNA [10,13].…”
Section: Discussionmentioning
confidence: 85%
“…Wan et al found EV-DNA to be superior compared to cfDNA in EGFR mutation detection in the early stage of non-small cell lung cancer. However, recent study on liquid biopsy of lung carcinoma patients found a higher mutant allele frequency of EGFR in cfDNA than EV-DNA [13]. Thus, it still remains under debate whether analysis of EV-DNA has any advantage over cfDNA in cancer detection.…”
Section: Introductionmentioning
confidence: 99%
“…Although ctDNA was reported to be derived from apoptotic or necrotic cancer cells as well as released from intact cells [14], it origin has not been clearly clarified. Recently, we reported a bimodal distribution of cfDNA long fragments of 5 kb and short fragments of 170 bp in patients with advanced lung cancer, and both fractions contained ctDNA [45,46]. The total amount of cfDNA is higher among patients with distant metastases, but this is more obvious with long fragment cfDNA.…”
Section: Future Perspectivesmentioning
confidence: 92%
“…On the basis of experiments with lung cancer cell lines, we found that long fragment cfDNA co-exists with extracellular vesicles (EVs). EVs are well known to mediate tumor progression by facilitating interaction between cancer cells and stromal cells [46]. Therefore, it is possible that long fragment cfDNA also contributes to tumor progression in concert with EVs.…”
Section: Future Perspectivesmentioning
confidence: 99%
See 1 more Smart Citation